2004
DOI: 10.1016/j.neuroscience.2004.05.003
|View full text |Cite
|
Sign up to set email alerts
|

P2Y receptor expression on astrocytes in the nucleus accumbens of rats

Abstract: The expression of purinoceptor (P2)Y-subtypes on astrocytes in vivo under physiological conditions and after stab wound injury was investigated. Reverse transcriptase-polymerase chain reaction with specific primers for the receptor-subtypes P2Y1,2,4,6,12 in tissue extracts of the nucleus accumbens of untreated rats revealed the presence of all P2Y receptor mRNAs investigated. Double immunofluorescence visualized with laser scanning microscopy indicated the expression of the P2Y1,4 receptors on glial fibrillary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
80
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(85 citation statements)
references
References 52 publications
4
80
1
Order By: Relevance
“…P2X4 is expressed at increased concentrations in response to tissue injury following spinal cord injury (Schwab et al, 2005), traumatic brain injury (Zhang et al, 2006) and in spinal cord microglia following peripheral nerve injury (Tsuda et al, 2003;Ulmann et al, 2008). After stab wound injury, P2X1 and P2X7 receptor immunoreactivity was observed on astrocytes that were previously absent (Franke et al, 2004). Cerebellar lesions produce up-regulation of P2X1 and P2X2 receptors in precerebellar nuclei (Florenzano et al, 2002).…”
Section: The Role Of P2x Receptors In Neuroinflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…P2X4 is expressed at increased concentrations in response to tissue injury following spinal cord injury (Schwab et al, 2005), traumatic brain injury (Zhang et al, 2006) and in spinal cord microglia following peripheral nerve injury (Tsuda et al, 2003;Ulmann et al, 2008). After stab wound injury, P2X1 and P2X7 receptor immunoreactivity was observed on astrocytes that were previously absent (Franke et al, 2004). Cerebellar lesions produce up-regulation of P2X1 and P2X2 receptors in precerebellar nuclei (Florenzano et al, 2002).…”
Section: The Role Of P2x Receptors In Neuroinflammationmentioning
confidence: 99%
“…P2Y 12 receptors, expressed on platelets, regulate various forms of inflammation and could either improve or worsen the scenario (Liverani et al, 2014a). In the CNS, P2Y 12 receptors are expressed on astrocytes, oligodendrocytes and the resting, ramified microglia executing surveillant functions (Amadio et al, 2014;Franke et al, 2004).…”
Section: The Role Of P2y Receptors In Neuroinflammationmentioning
confidence: 99%
“…Functional studies with astrocytes and oligodendrocytes have demonstrated a role for both P2Y 1 and P2Y 2 receptors in mediating ATP-evoked and IP 3 -dependent increases in [Ca 2+ ] i [20,80]. P2Y 2 Rs are upregulated in reactive astrocytes of the cortex and nucleus accumbens in rat due to mechanical injury, suggesting a role in modulating responses to trauma [126]. Furthermore, studies with astrocytic cells also suggest that P2Y 2 Rs play a role in astrocyte survival after injury [13,79].…”
Section: P2y 2 Receptors In Glial Cellsmentioning
confidence: 99%
“…In neural progenitor cells isolated from the subventricular zone of adult mouse brain, P2Y 2 R activation was shown to induce rapid and transient activation of the EGFR, ERK1/2, and CREB [160]. P2Y 2 R mRNA levels also were shown to increase during the acute and chronic stages of spinal cord injury [161] and with brain ischemia, mechanical injury to the nucleus accumbens, and brain trauma, an acute inflammatory response suggested to provide neuroprotection [126]. Other potential neuroprotective responses linked to P2Y 2 R function in primary cortical neurons include the activation of non-amyloidogenic APP processing [48].…”
Section: P2y 2 Receptors In Neuronsmentioning
confidence: 99%
See 1 more Smart Citation